Neurobehavioral Interpersonal Synchrony in Early Development: The Role of Interactional Rhythms - Markova, Gabriela; Nguyen, Trinh; Hoehl, Stefanie (Frontiers in Psychology, 2019)
Social interactions are essential for understanding others’ actions and their mental and affective states. Specifically, interpersonal coordination – also referred to as synchrony – allows actors to adjust their behaviors to one another and thus demonstrate their connectedness to each other. Much behavioral research has demonstrated the primacy of mutually synchronized social exchanges in early development. Additionally, new methodological advances now allow us to examine interpersonal synchrony not only at the behavioral and physiological, but also neural level. Nevertheless, it remains unclear how infants and their caregivers actually achieve interpersonal synchrony in their exchanges. Here we discuss recent evidence showing that adults provide rhythmical information during early social interactions with their infants, such as affective touch and singing. We propose that entrainment to these social rhythms underlies the formation of interpersonal synchrony and thus stimulates reciprocal interactions between infants and their caregivers.